Role of potassium fertilizer on growth and productivity of ARACHIS HYPOGAEA L. - صقر صباح (Latakia University Journal -Biological Sciences Series, 2020)
This research was carried out during 2014-2015 growing seasons to study the role of potassium fertilizer with 5 rates those (0.40.60.80.100)kg/h-1 on some growth parameters and productivity of Arachis hypogaea L. A randomized plot design with 3 replication. The result showed the following: -The application rates of potassium fertilizer 40-100 kg/h-1increase leaves number /plant , flowers number/plant, fresh weight of plant and pod number by plant. -The application of (60.80.100)kg/h-1gave significantly increase in leaves number , flowers number , fresh weight, pods number/plant compared with the control. -The application of (80.100)kg/h-1caused significant effect in leave number , flowers number , fresh weight, pods number/plant compared with the rate 40 kg/h-1.